Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10152-009-0164-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocyclops schminkei (Copepoda, Calanoida, Pseudocyclopidae): a new species from Okinawa

Abstract: Both genders of Pseudocyclops schminkei n. sp. are described from a pearl Wshery aquarium on Zamami Island, Okinawa, Japan; it is the 37th species of the genus. Pseudocyclops schminkei sp. nov. diVers from other species of the magnus species group in the shape of the lobes of distal exopodal segment of the male left leg 5, and the morphology of setae on middle and distal exopodal segment of male right swimming leg 2. Aspects of the morphology of P. xiphophorus and P. bilobatus are redescribed, and an unnamed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Although the results might be caused by a mesh selection, a second probable hypothesis is that Pseudocyclops lerneri is a weak swimmer, remaining close to the substrate during the night. It has been suggested that the general morphology of Pseudocyclops with plump body and short first antennae may limit their ability to remain in the water column (Chullasorn et al ., 2010). This would also explain the contrast in abundance in this study to previous Pseudocyclops studies which used subsurface net tows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results might be caused by a mesh selection, a second probable hypothesis is that Pseudocyclops lerneri is a weak swimmer, remaining close to the substrate during the night. It has been suggested that the general morphology of Pseudocyclops with plump body and short first antennae may limit their ability to remain in the water column (Chullasorn et al ., 2010). This would also explain the contrast in abundance in this study to previous Pseudocyclops studies which used subsurface net tows.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Pseudocyclops Brady, 1872 resembles a Cyclopoida copepod, characterized by its small plump body rarely exceeding 1 mm in length, short first antennules and the presence of strong spines on the outer margin of the exopodes of the swimming legs. This general body morphology is usually common in benthopelagic calanoids, which spend a good part of the diel cycle on or near the substrate (Chullasorn et al ., 2010). Pseudocyclops was first described as one of the few Calanoida that displayed bottom-living behaviour (Fosshagen, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Six naupliar stages were recovered from this Pseudocyclops population as described by (Chullasorn et al 2010) that inhabits aquaria at the John G. Shedd Aquarium (Chicago, IL, USA). Six naupliar stages are also known for Pseudocyclops umbraticus (Costanzo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Specimens of the new species were selected for analysis as well as the pseudocyclopid taxa ( Pseudocyclops juanibali Figueroa, and Pseudocyclops schminkei Chullasorn, Ferrari & Dahms, ). These taxa were used to add to the description of the new taxon and, along with additional species from GenBank, to improve the resolution of the current gene‐based phylogeny (Blanco‐Bercial, Bradford‐Grieve & Bucklin, ) (http://onlinelibrary.wiley.com/doi/10.1111/zoj.12141/suppinfo).…”
Section: Methodsmentioning
confidence: 99%